The Impact of Accessibility and Creativity on the Financial Performance of SMEs - Rofi'i, Yulianto Umar (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study examines the impact of accessibility and creativity on the financial performance of Micro, Small, and Medium Enterprises (MSMEs). Accessibility encompasses financial literacy and inclusion, both of which significantly influence the financial outcomes of MSMEs. Creativity enhances competitiveness and financial performance, particularly in product development and marketing. A quantitative research approach with a survey design was employed to gather data from 200 MSME operators in Indonesia. A questionnaire was used to assess accessibility, creativity, and financial performance. The results from multiple linear regression analysis revealed that accessibility and creativity positively affect the financial performance of MSMEs. Access to capital, technology, and training are key factors that improve business performance. Additionally, creativity in product development and marketing strategies contributes to financial growth. The findings suggest that enhancing accessibility and fostering creativity should be prioritized to strengthen MSMEs' competitiveness in the market. Policies that promote better access to financial resources and training for MSME operators are essential to ensuring the sector's sustainability and success.